2020
DOI: 10.3389/fpsyg.2019.02913
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Social Network Intervention Using Vlogs to Promote Physical Activity Among Adolescents: A Randomized Controlled Trial

Abstract: There is a need to stimulate physical activity among adolescents, but unfortunately, they are hard to reach with traditional mass media interventions. A promising alternative is to carry out social network interventions. In social network interventions, a small group of individuals (influence agents) is selected to promote health-related behaviors within their social network. This study investigates whether a social network intervention is more effective to promote physical activity, compared to a mass media i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 65 publications
0
39
0
3
Order By: Relevance
“…Specifically, there is a need for experimental research systematically varying the characteristics that are expected to increase the impact, including message factors (e.g., level of integration of the food promotion; Buijzen et al, 2010) and characteristics of the child-influencer relationship (e.g., level of identification; Folkvord et al, 2019). Vlogs with social media influencers may provide excellent stimulus materials for such experimental designs, with one recent randomized controlled trial providing a promising first step (Van Woudenberg et al, 2019). Comparing the effects of personally familiar with nonfamiliar vloggers on responses to the vlogs and physical activity behaviors, Van Woudenberg et al's findings showed that familiarity of the influencer improved adolescents' viewing time of and attitudes toward the vlogs and vloggers.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, there is a need for experimental research systematically varying the characteristics that are expected to increase the impact, including message factors (e.g., level of integration of the food promotion; Buijzen et al, 2010) and characteristics of the child-influencer relationship (e.g., level of identification; Folkvord et al, 2019). Vlogs with social media influencers may provide excellent stimulus materials for such experimental designs, with one recent randomized controlled trial providing a promising first step (Van Woudenberg et al, 2019). Comparing the effects of personally familiar with nonfamiliar vloggers on responses to the vlogs and physical activity behaviors, Van Woudenberg et al's findings showed that familiarity of the influencer improved adolescents' viewing time of and attitudes toward the vlogs and vloggers.…”
Section: Discussionmentioning
confidence: 99%
“…Our tips for effective communication with teens are based on the knowledge accumulated in the domains of media research and developmental psychology (e.g., Valkenburg & Piotrowski, 2017), our own research into youth communication and behavioral change (e.g., Smit, de Leeuw, Bevelander, Burk, & Buijzen, 2016;Van Woudenberg et al, 2020), and examples of successful evidence-based health campaigns targeting youth (e.g., Asbury, Wong, Price, & Nolin, 2008;Evans, Wasserman, Bertolotti, & Martino, 2002). Each time we are approached, by policymakers, communication professionals, or journalists, we start by sharing the tips.…”
Section: Ten Tips For Teen Campaigns To Curb the Corona Crisismentioning
confidence: 99%
“…It also common at this stage to experience significant emotional and behavioural problems, with loneliness at an emotional level standing out [ 38 ], alongside the abandonment of physical exercise, amongst other issues. Although students’ motivation towards physical activity (PA) is initially high in both sexes [ 39 , 40 ], diminishing interest and engagement is seen at increasing rates with advancing age [ 28 , 41 ]. Further, this decline is greater in females than in males.…”
Section: Discussionmentioning
confidence: 99%